DESCRIPTION OF THE CAUSES OF MDR-TB AT IBNU SINA HOSPITAL GRESIK - Purwanto, Cucuk Rahmadi; Widyamulya, Marissa; Okviasanti, Fanni (Universitas Airlangga, 2022)
Introduction: The causes of Multidrug Resistance Tuberculosis (MDR-TB) are very diverse; MDR-TB treatment, which takes a long time of approximately 18-24 months, so it becomes a severe health problem because of its rapid and increasing transmission. The purpose of this study was to describe the causes of the incident in Ibnu Sina Hospital Gresik. Methods: The method used in this research is a descriptive research method with a total of 55 respondents. In this study, data collection was carried out using a questionnaire. Results: The most common cause of MDR-TB in Ibnu Sina Hospital Gresik was a history of previous TB treatment with the results of the study obtained from 55 respondents, as many as 30 people (54.5%), and 25 people who did not have a history of previous treatment (45, 5%). Conclusions: Based on the study's results, the most common cause of MDR-TB at Ibnu Sina Hospital Gresik was a history of previous TB treatment. The causes of the minor incidence of MDR-TB are low family support and the subordinate role of PMO. Another more dominant factor is a history of contact with MDR-TB patients and non-adherence to taking medication.